Особенности теплового режима индукционно-динамического двигателя циклического действия - Болюх, В.Ф.; Щукин, И.С. (Електротехніка і електромеханіка, 2011)
A mathematical model describing thermal conditions of an inductive dynamic cyclic motor is developed. To determine the inductor and the armature temperatures which vary during the working process, a circuit and a field models are used. The effect of the armature idling, motion, and braking on the motor thermal conditions has been revealed. In the armature motion mode, the active elements temperature increase versus pulse repetition frequency, the armature height, the active elements cooling area, and the inductor cooling rate is studied. Experimental investigations conducted prove validity of the mathematical model and the calculation results.